2020
DOI: 10.3390/ani10040676
|View full text |Cite
|
Sign up to set email alerts
|

Transport to the Slaughterhouse Affects the Salmonella Shedding and Modifies the Fecal Microbiota of Finishing Pigs

Abstract: Contaminated pork is a significant source of foodborne Salmonellosis. Pork is contaminated at the slaughterhouse and the intestinal content is the predominant source of Salmonella for carcass contamination. The prevalence of Salmonella-positive pigs increases significantly when the time of transport to the slaughterhouse is longer than two hours. The hypothesis behind this study is that transport to the slaughterhouse increases the load of Salmonella in feces and determines a shift of the fecal microbiota in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Although most Salmonella-infected fattening pigs remain asymptomatic while at farms, stressful situations such as the transport to the abattoir or the time at lairage can increase the load of Salmonella in feces in those previously infected pigs [8], and also increase the susceptibility to infection of the healthy ones [9]. There is evidence that on-farm Salmonella status has a significant influence on Salmonella shedding at slaughter [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although most Salmonella-infected fattening pigs remain asymptomatic while at farms, stressful situations such as the transport to the abattoir or the time at lairage can increase the load of Salmonella in feces in those previously infected pigs [8], and also increase the susceptibility to infection of the healthy ones [9]. There is evidence that on-farm Salmonella status has a significant influence on Salmonella shedding at slaughter [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the microbial communities were very similar for groups T1 and T2 for all samples, showing phages did not have a detectable negative impact on the intestinal microflora. Interestingly, the relative abundance of Prevotellaceae was consistently higher in all samples collected from group T2, which is the family that has been previously shown to be associated with healthy pigs ( 40 , 41 ). Consistent with our study, another pig phage challenge study also observed that the relative abundance of the Prevotellaceae was higher in phage treated groups ( 42 ).…”
Section: Discussionmentioning
confidence: 66%
“…Salmonella can colonize pigs' gut, although most of them remain healthy carriers and the stress related to farm management, transportation, and early slaughtering stages (from unloading to stunning) may increase the prevalence of infected pigs entering the slaughtering process [11][12][13]. When animals are processed, contamination of pig carcasses can result from the skin, the intestinal contents, infected tissues, other carcasses, or slaughterhouse surfaces [14][15][16].…”
Section: Introductionmentioning
confidence: 99%